AGROBİOLOGİCAL PARAMETERS OF SOME LOCAL, AND İNTRODUCED COLLECTİBLE GRAPE VARİETİES, GROWN İN THE CONDİTİONS OF THE ABSHERON DİSTRİCT - V.S.Salimov, A.S.Huseynova, S.Ş. Abdulaliyeva, M.M. Alekberova, F.A.Aslanova, (Chelonian Research Foundation, 2024)
The article presents the results of the research work on the study of agrobiological parameters, morphological and technological characteristics of some local (Ag pishraz, Gara kechimemesi, Gara pishraz, Gara urza, Gara khatyny, Gozal uzum, Gomushimeme, Galshan, Ganja kechimemesi, Khalbasar) and introduced (Danaburnu, Dekabrskiy, Janjal kara, Dnestrovskiy rozovy, Doina, Ichkimar, Cardinal, Kuljinskiy, Moldova, Muscat Italian, Pobeda, Presentabill, Sultani, Taifi pink, Tuya tish) collectible table grape varieties grown in the conditions of the Absheron district. In the course of the scientific-research work, classical and modern research methods were used, such as the Mann-Whitney Wilcoxon U-criterion, the Student's t-criterion, the Pirson χ2 criterion, mathematical and statistical analysis, digital description of varieties according to the international ampelographic descriptors and assessment of prospects of varieties according to the “ideal variety” innovative model, proposed by the OIV, etc. As a result of mathematical and statistical processing of the data obtained during the study, it was revealed that the yield indicators of the studied grape varieties Ichkimar, Muscat Italian, Pobeda, Presentabill, Taifi pink and Tuya tish significantly exceed the control variety Danaburnu. For the rest of the varieties, the difference with the control variety was insignificant. Keywords: grapes, bunch, introduced variety, yield, quality, mathematical and statistical analysis, collection garden